MODEL PENGEMBANGAN KURIKULUM SISWA CERDAS ISTIMEWA MATA PELAJARAN BAHASA INDONESIA - Sujinah Sujinah (Fakultas Sastra Universitas Negeri Malang, 2012)
Without the provision of differentiation service for gifted students, the program would be so called gifted student without gifted program. The predicted danger that would arise for gifted students in normal service is that the students experience underachievement; therefore, it is necessary to apply the differentiated- curriculum model for gifted students. This article describes not only a curriculum model that is used in the school with its gifted students program or acceleration class but also the validity, practicality, and effectiveness of the model. The method used was a combination model of RDR (research, development, research) with R2D2 (recursive, reflective, design, and development) with adaptations, modifications, and/or a particular transformation. The data were gathered through documentation of data collection techniques, unstructured interviews, questionnaires, and observation. The curriculum was developed under the procedures of: Pemendiknas No. 22 of 2006, Identification, Escalation, Essence, Mapping, organization and allocation of time